Predicting the Potential of Black Seed Bioactive Compounds against Potato Virus X Using In Silico Molecular Docking - Adham Ezz El-Regal Mahmoud; Atef Shoukry Sadik; Ahmed Mahdy (Novel Research in Microbiology Journal)
This study presents a comprehensive analysis of the physicochemical, pharmacokinetic, and molecular docking properties of black seed (Nigella sativa) bioactive compounds-Nigellicine, Carvacrol, Nigellidine, and Thymoquinone-compared to the antiviral drug Ribavirin, using SwissADMET predictions and molecular docking simulations. The physicochemical profiles revealed that all black seed compounds are drug-like, with molecular weights under 500 g/mol, low molecular flexibility, and adherence to Lipinski’s rule. Black seed compounds exhibit high gastrointestinal absorption and positive blood-brain barrier (BBB) permeability, suggesting better bioavailability and potential CNS activity than Ribavirin. Notably, Carvacrol and Nigellidine inhibit key cytochrome P450 enzymes (CYP1A2 and CYP2D6), which could lead to drug-drug interactions. Molecular docking results demonstrated that Nigellidine showed the highest binding affinity and docking score against both PVX replicase (-8.9 kcal/mol) and PVX coat protein (-8.1 kcal/mol), outperforming Ribavirin. Nigellicine also exhibited promising docking scores, comparable to Ribavirin. In contrast, Carvacrol and Thymoquinone showed weaker interactions. These findings suggest that Nigellidine and Nigellicine have superior potential as antiviral agents, with stronger and more diverse interactions than Ribavirin, especially in targeting PVX proteins. This study highlights the therapeutic potential of black seed compounds for antiviral drug development and provides a foundation for future experimental validation.